2021
DOI: 10.21203/rs.3.rs-203952/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimization of moist and oven-dried bacterial cellulose production for functional properties

Abstract: Bacterial cellulose (BC) is a natural polymer with properties suitable for tissue engineering and possible applications in scaffold production. However, current procedures have limitations in obtaining BC pellicles with the desired structural, physical, and mechanical properties. Thus, this study analyzed the optimal culture conditions of BC membranes and 2 types of processing: draining and oven-drying. The aim was to obtain BC membranes with properties suitable for a wound dressing material. Two studies were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Figure 3 shows the alternative culture media used for BNC production. It is possible to note the predominance of kombucha-like culture media (5 papers, 62.5%), which 40% were supplemented with corn syrup (DIMA et al, 2017) or calcium carbonate and yeast extracts (BODEA et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows the alternative culture media used for BNC production. It is possible to note the predominance of kombucha-like culture media (5 papers, 62.5%), which 40% were supplemented with corn syrup (DIMA et al, 2017) or calcium carbonate and yeast extracts (BODEA et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Bodea and collaborators (2021) supplemented the kombucha-like medium with calcium carbonate, despite the reason was not informed in their paper. It was found that the inoculum and fermentation time did not influence the homogeneity of obtained BNC membranes, as well as a two-step effective purification process for BNC (BODEA et al, 2021). Also, nanofibers' average diameter was between 40.6-51.33 nm and the CrI was, unfortunately, not measured.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The dense cellulose network led to less water accumulation between fibers, resulting in a 7.83% -26.53% decrease in the BC-CMC initial wet weight compared to the wet weight of BC. According to a study by Bodea et al, the first drying of BC brings the fibers closer together, which leads to a more compact structure [45]. Absorbed water in BC limits the interactions between fibers with the competitive hydrogen-water-cellulose bonds.…”
Section: Rehydration Of Bc In-situ Modified Samplesmentioning
confidence: 99%
“…Absorbed water in BC limits the interactions between fibers with the competitive hydrogen-water-cellulose bonds. Water in the BC pellicle is crucial to achieving some mechanical properties since water can serve as a plasticizer [45,46]. Despite the decrease in the initial wet weight of the CMC-BC composite compared to the BC, its rehydration increased by 102.30% (Fig.…”
Section: Rehydration Of Bc In-situ Modified Samplesmentioning
confidence: 99%